1999
DOI: 10.1001/jama.282.16.1539
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber, Weight Gain, and Cardiovascular Disease Risk Factors in Young Adults

Abstract: Fiber consumption predicted insulin levels, weight gain, and other CVD risk factors more strongly than did total or saturated fat consumption. High-fiber diets may protect against obesity and CVD by lowering insulin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
364
3
13

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 620 publications
(414 citation statements)
references
References 34 publications
34
364
3
13
Order By: Relevance
“…Evidence that dietary fibre intake prevents obesity is strong. Fibre intake is inversely associated with body weight and body fat (31)(32)(33) . In a prospective cohort study among US female nurses, Liu et al (32) found that women in the highest quintile of dietary fibre intake had a 49 % lower risk of major weight gain than did women in the lowest quintile, which suggested weight gain was inversely associated with the intake of high-fibre, wholegrain foods.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that dietary fibre intake prevents obesity is strong. Fibre intake is inversely associated with body weight and body fat (31)(32)(33) . In a prospective cohort study among US female nurses, Liu et al (32) found that women in the highest quintile of dietary fibre intake had a 49 % lower risk of major weight gain than did women in the lowest quintile, which suggested weight gain was inversely associated with the intake of high-fibre, wholegrain foods.…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of not only undernutrition, but also overweight and obesity have been reported in old people McCormack, 1997;Ritchie et al, 1997;Jensen & Rogers, 1998;Millen et al, 2001;Jensen & Friedmann, 2002). Ludwig et al, 1999;La Vecchia et al, 2001, Hu & Willett, 2002. Since the prevalence of these diseases is much higher in older age groups, nutrition is, thus, of special importance in late life.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat intake has long been assumed to be a major nutritional contributing factor to obesity, but the results of observational studies have been mixed (Appleby et al , 1998;Ludwig et al, 1999;Stookey, 2001;Sasaki et al, 2003;Spencer et al, 2003;Howarth et al, 2005). Although this inconsistency may be due to selective underestimation of dietary fat intake by obese people (Goris et al, 2000), the potential role of dietary carbohydrate in the development of obesity has thus become an important question, because the intake of another macronutrient, protein, is fairly constant in normal diets.…”
Section: Introductionmentioning
confidence: 99%